Word of Mouth sebagai Efek Respon Positif dari Kepuasan Konsumen dan Dampaknya pada Pembelian Kembali: Studi Kasus Mahasiswa sebagai Konsumen Yoghurt Activia - Sriwardiningsih, Enggal (Binus Business Review, 2011)
This research want to know word of mouth as respon positive effect from consumen satisfaction and impact to repurchase. Methodology used provement of statistical test, liket scala, and a path analysis. The data came from primer sources by cross section with quesioner amount one hundred participan. Result of this riset significanly word of mouth as efek respon positif from consumen satisfaction and impact to repurchase, but interesting found that no signifikan relation between consumen satisfaction with repurchase, for his product may be another kind of consumer behavior work.